KESESUAIAN PERAN GURU PADA STRATEGI RESOLUSI KONFLIK UNTUK MENINGKATKAN EMPATI DAN KETERAMPILAN SOSIAL SISWA DI SEKOLAH DASAR - Mahzumi, Ahmad; Hitta Alfi Muhimmah; Budi Purwaka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Conflicts in elementary school environments are a common phenomenon and can affect relationships among students as well as their social-emotional development. Teachers, as facilitators of learning, play a crucial role in implementing conflict resolution strategies that not only solve problems but also enhance students' empathy and social skills. The purpose of this study is to evaluate how effectively teachers can use conflict resolution techniques to help elementary school students become more empathetic and socially adept. Social and emotional development in students can be influenced by frequent conflicts in elementary school settings. Through an educational approach, teachers can effectively guide and facilitate conflict resolution. This study employs a qualitative methodology and a case study design, which includes document analysis, interviews, and observations in multiple elementary schools. According to the research findings, instructors can enhance students' social skills—such as their capacity for cooperation, clear communication, and peaceful problem-solving—by acting as mediators, facilitators, and role models in implementing empathy-based conflict resolution techniques. More structured instruction is needed to foster a harmonious and productive learning environment.